2020
DOI: 10.14260/jemds/2020/67
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Stigma towards Mental Illness among Medical Students? - A Systematic Review of the 1997-2018 Literature

Abstract: BACKGROUND The stigma associated with mental illness is a global public health problem 3 , having worse consequences than the disorders themselves 4. The objective of this study is to review the literature on the stigma towards mental illness in medical students and know about its presence. METHODS Following the PRISMA 9 methodology, a systematic review is carried out in PubMed, Web of Science (WOS) and Cochrane Library. We proceed to the reading of the abstracts of a total of 67 manuscripts, 38 of which are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Among the various interventions to prevent stigma (Corrigan et al, 2018;Pandian et al, 2020;Rüsch & Kösters, 2021), direct contact with people with mental illness appears to be more effective than education with video exposure (Gervás et al, 2022) and group discussion (Pandian et al, 2020), which have shown high efficacy (Heim et al, 2019;Rezvanifar, Shariat, Shalbafan, Salehian, & Rasoulian, 2022). Our results suggest that it may be necessary to enrich educational interventions with more significant interaction with patients (Lien et al, 2021;Sandhu, Arora, Brasch, & Streiner, 2019), considering that the most appropriate strategies allow such coexistence in an educational context that prioritizes the clarification of beliefs and the detection of preconceived stigmatizing attitudes (Balon et al, 2017;Heim et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Among the various interventions to prevent stigma (Corrigan et al, 2018;Pandian et al, 2020;Rüsch & Kösters, 2021), direct contact with people with mental illness appears to be more effective than education with video exposure (Gervás et al, 2022) and group discussion (Pandian et al, 2020), which have shown high efficacy (Heim et al, 2019;Rezvanifar, Shariat, Shalbafan, Salehian, & Rasoulian, 2022). Our results suggest that it may be necessary to enrich educational interventions with more significant interaction with patients (Lien et al, 2021;Sandhu, Arora, Brasch, & Streiner, 2019), considering that the most appropriate strategies allow such coexistence in an educational context that prioritizes the clarification of beliefs and the detection of preconceived stigmatizing attitudes (Balon et al, 2017;Heim et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Among the limitations of this study, some are that it was developed in only one generation of students after one seminar and only in one medical school (Gervás et al, 2022;Lien et al, 2021;Waqas et al, 2020). Furthermore, no questions were asked about the students' previous exposure to people with any disease or their representation by the media.…”
Section: Limitationsmentioning
confidence: 99%
“…Stigma has a multifaced nature ( Link and Phelan, 2001 ) referring to: (1) labeled differences, that is distinguishing and categorizing human variations; (2) stereotypes, which are associated with negative generalizations; (3) separation, which defines the divide between the mainstream and the marginalized; (4) status loss and discrimination, emphasizing the disadvantages faced by those marginalized; (5) power, underscoring the societal hierarchies that perpetuate discrimination; and (6) emotional reactions, capturing feelings from shame in the stigmatized to disgust in the stigmatizers ( Link and Phelan, 2001 ). Stigma is a widespread phenomenon among university students, with prevalence rates ranging from 21 to 97% ( Tzouvara et al, 2016 ; Zolezzi et al, 2017 ; Gervas et al, 2020 ). Stigma influences individuals’ perception of responsibility regarding the emergence and maintenance of their health status and may impact resilience ( Boardman et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of stigma in students is important because they can become the target audience for anti-stigma programmes (11,12). A recent review concluded that the presence of stigma toward MI among medical university students is widespread, with a prevalence of up to 97% (13). Stigmatizing attitudes and desire for more social distance have also been found among psychology students (14,15).…”
Section: Introductionmentioning
confidence: 99%